Special functions, partial differential equations, and harmonic analysis : in honor of calixto p. calderon - Stokolos, Alexander M.; Urbina, Wilfredo; Georgakis, Constantine (Springer Proceedings in Mathematics & Statistics, 2014)
This volume of papers presented at the conference in honor of Calixto P. Calderón by his friends, colleagues, and students is intended to make the mathematical community aware of his important scholarly and research contributions in contemporary Harmonic Analysis and Mathematical Models applied to Biology and Medicine, and to stimulate further research in the future in this area of pure and applied mathematics.